A Scanner and Parser for Z Specifications - Siregar, Maria Ulfah; Derrick, John (IJID (International Journal on Informatics for Development), 2018)
This paper describes our research on implementing a scanner and parsers for Z specifications. Rather to code them from scratch, we use tools that have specialities on creating such tasks. These tools generate several Java files which can be integrated with a main program in Java. Our research could produce a scanner and parser for Z specifications. These tools could benefit Z specifications to be studied further.